2014
DOI: 10.4314/agrosh.v13i3.3s
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Different Concentrations And Frequency of Foliar Application of <i>Moringa Extract</i> on Growth & Yield of Onion, <i>Allium cepa</i> Lam

Abstract: Field trials were conducted between 2010/11 and 2011/12 at the Forestry Research Institute of o Nigeria (FRIN) of Federal College of Forestry Mechanization Afaka, Kaduna experimental site, 10 1o 1 03 N, 07 21 E and 644m above sea level in the Northern guinea savanna agro-ecological zone during 2011 to 2012 dry season. The objective was to evaluate the effect of different concentration and frequency of foliar application of Moringa extract on growth and yield of Onion (Allium cepa Lam). Fresh Moringa oleifera s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 2 publications
2
4
0
1
Order By: Relevance
“…Moniruzzaman et al (2007) also reported higher seed yield of okra at the narrowest spacing and this also corroborates the findings of Falodun and Ogedegbe (2016) who recorded higher pod yield of okra at narrower spacing compared to wider spacing. The significant increase in some vegetative characters and yield with the 15 t/ha application of swine manure is similar to the work of Curuk et al (2004) who reported increases in fruit yield after high manure input compared to customary inorganic fertilization and this further supports the work of Mohammed et al (2013) who observed an increase in growth and yield of onion applied with moringa extract.…”
Section: Discussionsupporting
confidence: 88%
“…Moniruzzaman et al (2007) also reported higher seed yield of okra at the narrowest spacing and this also corroborates the findings of Falodun and Ogedegbe (2016) who recorded higher pod yield of okra at narrower spacing compared to wider spacing. The significant increase in some vegetative characters and yield with the 15 t/ha application of swine manure is similar to the work of Curuk et al (2004) who reported increases in fruit yield after high manure input compared to customary inorganic fertilization and this further supports the work of Mohammed et al (2013) who observed an increase in growth and yield of onion applied with moringa extract.…”
Section: Discussionsupporting
confidence: 88%
“…The overall effects of all the growth enhancing components in moringa leaf extract (MLE) have made it a novel and marvelous natural bio-stimulant. Interestingly, many recent scientific reports have highlighted that MLE application to plant can provide beneficial nutrient elements, improve antioxidant defense system and enhance vegetative as well as reproductive growth resulting in higher yield and economic benefits under stressed and non-stressed situations (Abohassan and Abusuwar, 2018;Prabhu et al, 2010;Aluko et al, 2017;Hala et al, 2017;Merwad, 2017;Matthew, 2016;Emongor, 2015;Rady and Mohamed, 2015;Ozobia, 2014;Mohammed et al, 2013;Abdalla, 2013;Mvumi et al, 2012Mvumi et al, , 2013. Vegetables are enriched with different vitamins, minerals, and phytochemicals.…”
Section: Introductionmentioning
confidence: 99%
“…Por conseguinte, a escolha da espécie de cebola utilizada emerge como uma variável que pode ser manipulada, influenciando nos resultados obtidos (Messias et al, 2021). Além disso, não devemos negligenciar o impacto da variação na concentração da substância, uma vez que essa também se configura como uma variável suscetível de interferir nos desfechos experimentais como é possível identificarnos estudos de (Mohammed et al, 2013;Hidangmayum;Sharma, 2017;Santos et al, 2018).…”
Section: Fonte: Autoresunclassified